2017
DOI: 10.1016/j.arth.2016.10.017
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Solid Organ Transplant History on Inpatient Complications, Mortality, Length of Stay, and Cost for Primary Total Hip Arthroplasty Admissions in the United States

Abstract: Background As the prevalence of and life expectancy after solid organ transplantation increases, some of these patients will require total hip arthroplasty (THA). Immunosuppressive therapy, metabolic disorders, and post-transplant medications may place transplant patients at higher risk of adverse events following surgery. The objective of this study was to compare inpatient complications, mortality, length of stay (LOS), and costs for THA patients with and without solid organ transplant history. Methods A r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 33 publications
1
40
0
Order By: Relevance
“…SOT patients also had longer length of hospital stay. One possible explanation is the higher degree of medical care provided to SOT patients as seen in other non–COVID‐related hospitalizations 22,23 . Another possibility is that the SOT patients in our study had a higher proportion of critical disease and ICU needs (although not found statistically significant).…”
Section: Discussionmentioning
confidence: 56%
“…SOT patients also had longer length of hospital stay. One possible explanation is the higher degree of medical care provided to SOT patients as seen in other non–COVID‐related hospitalizations 22,23 . Another possibility is that the SOT patients in our study had a higher proportion of critical disease and ICU needs (although not found statistically significant).…”
Section: Discussionmentioning
confidence: 56%
“…Of these, articles were excluded after screening their titles, abstracts, and full-text reviews. Thus, 10 articles 5 13 14 15 16 17 18 19 20 21) were eligible for qualitative and quantitative data syntheses. Regarding study selection, the agreement between the two reviewers was almost perfect at the title review and abstract review stages (κ=0.814 and κ=0.849, respectively) as well as the full-text review stage (κ=1.0).…”
Section: Resultsmentioning
confidence: 99%
“…An increased risk of perioperative complications, longer length of stay, and higher admission cost following THA were associated with a patient history of solid organ transplant and hematologic malignancies 33,34 .…”
Section: Patient Factors In Relation To Outcomes Medical Comorbiditiesmentioning
confidence: 99%